Test Bench for Functionality and Reliability of Power Protection Devices - STANCA Aurel Cornel; ORDACE Anamaria; OGRUTAN Petre Lucian; ACIU Lia Elena (TEM Journal, 2018)
This paper presents a test bench, designed for testing the functionality and reliability of a icrocontroller based device meant to protect the consumers connected to the power grid. By means of this test system, the testing device is repeatedly applied to overvoltages, overloads, electric ground leakages and an electric arc. The test system checks up the load disconnection, as well as its automated reconnection, and in the end it generates a test report.